The Vision of Civilization as Da'wah: A Critical Analysis of the Implementation of Scientific Integration at UIN Alauddin Makassar - Pababbari, Musafir; Takbir, Muhammad (KOMUNIDA : Media Komunikasi dan Dakwah, 2025)
The knowledge integration is an effort to dialogue science (secular) and religion (Islam). This effort also is the basis for the institutional change of Islamic higher education from the State Islamic Institute (IAIN) to the State Islamic University (UIN). This study specifically critically examines the implementation of integration of knowledge at UIN Alauddin in the time interval 2015-2023 - two periods of the Rector's leadership, namely 2015-2019 and 2019-2023. The aim is to see the development of the face of integration of knowledge on a campus that claims to be a campus of civilization. Because this is a compass that covers all production of science. This study uses a qualitative-descriptive method. Data was collected using observation, in-depth interviews, and document searches, and then analyzed descriptively. This research is shown by the decreasing number of research allocations on this theme from year to year. In 2018 and 2019 the number of integration research was 40 titles, while in 2022 and 2023 there were only 19 titles. This reality in turn has implications for the passion for the transformation of knowledge integration in the field of education and teaching. In short, the implementation of knowledge integration at UIN Alauddin tends to be procedural-symbolic.